Impact of Fintech Adoption, MSME Digital Readiness, and Regulatory Environment on Financial Performance in Indonesia - Antoni, Antoni; Judijanto, Loso; Supriadi, Adih; Rahman Halik, Bachtiar (Westscience Press, 2024)
This study investigates the impact of Fintech Adoption, MSME Digital Readiness, and the Regulatory Environment on Financial Performance in Indonesia's micro, small, and medium enterprises (MSMEs). Using a quantitative analysis with a sample size of 170, data was collected using Likert scales and analyzed through Structural Equation Modeling - Partial Least Squares (SEM-PLS 3). Results indicate that all relationships hypothesized (Fintech Adoption, MSME Digital Readiness, and Regulatory Environment -> Financial Performance) are positively significant. Specifically, Fintech Adoption positively influences Financial Performance, MSME Digital Readiness shows a significant positive impact on Financial Performance, and a supportive Regulatory Environment enhances Financial Performance significantly. These findings underscore the importance of technological integration, digital preparedness, and regulatory support in bolstering financial outcomes for MSMEs in Indonesia.